Aesthetic Rehabilitation of a Severe Dental Fluorosis Case with Ceramic Veneers: A Step-by-Step Guide - Aminah M. El Mourad (Case Reports in Dentistry)
The selection of an appropriate treatment plan for cases of dental fluorosis depends on the severity of the condition. Ceramic veneers are considered the treatment of choice for moderate to severe cases of fluorosis given the optimum aesthetics, wear resistance, biocompatibility, and long-term results of these veneers. This case report describes a step-by-step rehabilitation of fluorosed teeth, using ceramic veneers in a 26-year-old Yemeni male. The patient presented at the restorative dentistry clinics at King Saud University complaining of an unpleasant smile and generalized tooth discoloration.